Botulinum Toxin in Dentistry: A Literature Review - Lima, Luísa Sobrino Reis (2020)
Objective: the aim of this study was, through a literature review, to discuss the mechanism of action, the botulinum toxins use characteristics, their aesthetic and therapeutic indications, preparing a practical and illustrated content so that undergraduate dentistry students and dental surgeons have a first contact with the topic. Materials and Methods: a survey was conducted in Google Scholar, Pubmed and Scielo databases, using the keywords: Botulinum Toxins, Dentistry, Botulinum Toxins, Dentistry. 32 articles in Portuguese and English, published from 2008 to 2019, in their full and free versions, were selected. Articles that did not directly address to the topic were excluded. Results: it is known that Botulinum Toxin Type-A (BTX-A) has numerous applications, and in dentistry it presents numerous aesthetic and therapeutic indications. The toxin was effective in the treatment of bruxism, temporomandibular disorders, masseter hypertrophy, gingival smile, smile asymmetry, sialorrhea and implantology. Because of that, it tends to be increasingly present in dental offices. Conclusion: it was possible to conclude that, when used by trained professionals who follow proper protocols, it is a minimally invasive and safe treatment, capable of improving patients’ quality of life.